The association of long-term blood pressure variability with hemodialysis access thrombosis - Hsieh, Mu-Yang; Cheng, Chi-Hung; Chen, Chiu-Hui; Liao, Min-Tsun; Lin, Chih-Ching; Yang, Ten-Fang; Chuang, Shao-Yuan; Wu, Chih-Cheng (Frontiers in Cardiovascular Medicine, 2022)
Background: Blood pressure variability (BPV) is an important risk factor for cardiovascular events in hemodialysis patients. We sought to determine the impact of blood pressure variability on hemodialysis access thrombosis. Methods: We enrolled 1011 prevalent hemodialysis patients from 12 hemodialysis centers since January 2018 and followed them until December 2020. Predialysis blood pressure was assessed at 12-week intervals. The coefficient of variation derived from 36 consecutive blood pressure measurements was used as the metric for variability. The primary outcome was incident hemodialysis access thrombosis. Linear regression models were used to assess factors associated with BPV at baseline. Kaplan-Meier curves of the time until vascular access events were drawn and log-rank tests were calculated. Cox proportional hazards models were performed to assess the association of BPV with incident vascular access events. Results: The average coefficient of variance for systolic blood pressure variability was 10.9%. BPV was associated with age, body mass index, mean blood pressure, diabetes, coronary and peripheral artery disease, history of access dysfunction, graft access, intradialytic hypotension, and use of antihypertensive medications. There were 194 access thrombosis events and 451 access stenosis events during a median follow-up period of 30 months. After adjustment of potential confounding factors, BPV was associated with increased risk of access thrombosis (hazard ratio=1.27, 95% confidence interval [CI], 1.18-1.44, per 1 standard deviation increase in blood pressure variability). The patients in the highest BPV quartile had 2.45 times the risk of thrombosis (CI, 1.62-3.70). The association was independent of average blood pressure, intradialytic hypotension, and comorbidities. Similar trends of association were found in the subgroups analyzed. Comparative analysis using a time-varying variable model and different metrics of blood pressure variability showed consistent results. Conclusions: Our findings underscored the impact of blood pressure fluctuation on vascular access thrombosis.